Eggs and eggshells of Crocodylomorpha from the Upper Jurassic of Portugal - Russo, João Paulo Vasconcelos Mendes (2016)
Crocodylomorph eggs are relatively poorly known in the fossil record when compared with skeletal remains, which are found all over the world, or when compared with dinosaur eggs. Herein are described crocodiloid eggshells from the Upper Jurassic Lourinhã Formation of Portugal, recovered from five sites: Cambelas (clutch), Casal da Rola, Peralta (eggshell fragments), and Paimogo North and South (three partial crushed eggs and eggshell fragments). The clutch of Cambelas, composed of 13 eggs, is the only sample not found in association with dinosaur eggshells. Morphological characters of the eggshells described herein, such as shell units and microstructure, are consistent with the crocodiloid morphotype. As such, this material is assigned to the oofamily Krokolithidae, making them the oldest known crocodylomorph eggs so far and the best record for eggs of non-crocodylian crocodylomorphs. Two new ootaxa are erected, Suchoolithus portucalensis oogen. et oosp. nov, for the clutch of Cambelas, and Krokolithes dinophilus, oosp. nov., for the remaining eggshells. The basic structure of crocodilian eggshells has remained stable since at least the Late Jurassic. Additionally, the findings suggest previously unknown biological associations with contemporary archosaurs, shedding light on the poorly understood egg morphology, reproduction strategies and paleobiology of crocodylomorphs during the Late Jurassic.